Hydroxychloroquine in rheumatic autoimmune disorders and beyond. Issue 8 (26th July 2020) - Nirk, Eliise Laura; Reggiori, Fulvio; Mauthe, Mario
Abstract: Initially used as antimalarial drugs, hydroxychloroquine (HCQ) and, to a lesser extent, chloroquine (CQ) are currently being used to treat several diseases. Due to its cost‐effectiveness, safety and efficacy, HCQ is especially used in rheumatic autoimmune disorders (RADs), such as systemic lupus erythematosus, primary Sjögren's syndrome and rheumatoid arthritis. Despite this widespread use in the clinic, HCQ molecular modes of action are still not completely understood. By influencing several cellular pathways through different mechanisms, CQ and HCQ inhibit multiple endolysosomal functions, including autophagy, as well as endosomal Toll‐like receptor activation and calcium signalling. These effects alter several aspects of the immune system with the synergistic consequence of reducing pro‐inflammatory cytokine production and release, one of the most marked symptoms of RADs. Here, we review the current knowledge on the molecular modes of action of these drugs and the circumstances under which they trigger side effects. This is of particular importance as the therapeutic use of HCQ is expanding beyond the treatment of malaria and RADs. Abstract : Hydroxychloroquine has been heavily discussed in the context of COVID19, but this anti‐malarial drug is primarily used in rheumatic autoimmune disorders (RADs). This comprehensive review recapitulates our knowledge on the mode of action of this drug in RADs, and on its potential applications and side effects.